PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL MODERASI - Kansah, Dinda Dwi; Utaminingtyas, Tri Hesti; Fauzi, Achmad (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This research aims to analyze human resource competence and internal control systems on the quality of regional government financial reports by utilization of information technology as a moderating variable, which is still rarely researched. The number of samples in this research was 62 employee respondents in the Finance/Accounting Subdivision of the Bekasi City OPD using a purposive sampling method in selecting samples. The data used in this research is primary data collected using a questionnaire. The data analysis technique used is moderated regression analysis at a significance level of 5% with the help of SPSS version 26 software. This research produces findings that human resource competency positively affects the quality of Bekasi City regional government financial reports. In contrast, the internal control system negatively affects the quality of Bekasi City regional government financial reports. The utilization of information technology does not moderate the influence of human resource competence on the quality of the Bekasi City regional government financial reports, while the utilization of information technology strengthens the influence of the internal control system on the quality of Bekasi City regional government financial reports.